Penggunaan Media PPT Interaktif dalam Pembelajaran IPA untuk Melatihkan Keterampilan Komunikasi Siswa SMP - Aumita Dreamyseila; ⁠Dyah Astriani (CV. Ulil Albab Corp, 2026)
This study was motivated by the low level of students' communication skills in science learning, both oral and written communication. This study aims to describe students' communication skills, learning implementation, and student responses through the use of interactive PPT media on vibration and wave material. The study used a quantitative approach with a one-group pretest-posttest pre-experimental design. The research was conducted at SMP Muhammadiyah 2 Taman with 31 students in class VIII-G as subjects. Data collection techniques included tests (pretest and posttest), observation, questionnaires, and media validation. The research instruments consisted of a written communication test, an oral communication observation sheet, learning implementation, a student response questionnaire, and a media validation sheet. The data were analyzed using the Shapiro–Wilk normality test, paired sample t-test, and Cohen's d effect size. The results showed a significant difference between the pretest and posttest scores (p < 0.05) with an effect size of 2.490 (large category). The average score increased from 61.2% to 85.4%. The implementation of learning reached 98% (very good category) and student response was 91% (very good category). The media was declared highly valid with a percentage above 95%. The conclusion of this study shows that the use of interactive PPT media is effective in training students' communication skills. It is recommended that teachers optimize the division of roles and time in the implementation of learning.